VHCF properties of nitrided 18Ni maraging steel thin sheets with different Co and Ti content. Issue 5 (28th September 2014) - Schuller, R.; Fitzka, M.; Irrasch, D.; Tran, D.; Pennings, B.; Mayer, H.
Abstract High cycle fatigue (HCF) and very high cycle fatigue (VHCF) properties of two 18Ni maraging steels with different cobalt and titanium content and similar static strength are investigated. Ultrasonic fatigue tests are performed with thin sheets with nitrided surfaces at load ratio R = 0.1. The specimens are mounted on a carrier and are forced to joint vibrations at approximately 20 kHz. The increase of Co content and the elimination of Ti improved the HCF and VHCF strength of 18Ni maraging steel. TiN inclusions if Ti is present and Al2O3 inclusions in the Ti free material with sizes (areaINC)1/2 smaller than 10 µm were preferential crack initiation locations. Considering inclusions as initial cracks, the minimum stress intensity range for VHCF failure is 1.2 MPam1/2 for TiN inclusions and 1.8 MPam1/2 for Al2O3 inclusions. Data scatter may be slightly reduced if lifetimes are presented versus stress amplitudes multiplied by (areaINC)1/12 rather than in an S–N diagram.